The love songs of W.E.B. Du Boise [compact disc, unabridged] : a novel - Jeffers, Honorée Fanonne, 1967- (Harper Audio, 2021)
The 2020 National Book Award nominated poet makes her fiction debut with this magisterial epic, an intimate yet sweeping novel with all the luminescence and force of Homegoing; Sing, Unburied, Sing; and The Water Dancer, that chronicles the journey of one American family, from the centuries of the colonial slave trade through the Civil War to our own tumultuous era.